A mechanical system for tensile testing of supported films at the nanoscale. (23rd July 2018) - Pantano, Maria F; Speranza, Giorgio; Galiotis, Costas; Pugno, Nicola
Abstract: Standard tensile tests of materials are usually performed on freestanding specimens. However, such requirement is difficult to implement when the materials of interest are of nanoscopic dimensions due to problems related to their handling and manipulation. In the present paper, a new device is presented for tensile testing of thin nanomaterials, which allows tests to be carried out on specimens initially deposited onto a macroscopic pre-notched substrate. On loading, however, no substrate effects are introduced, allowing the films to be freely stretched. The results obtained from a variety of thin metal or polymeric films are very promising for the further development of this technique as a standard method for nanomaterial mechanical testing.